Behavior of platinum in the system of the matte-slag in the processing of copper-nickel materials - Amdur A.; Selivanov E.; Fedorov S.; Pavlov V.; Krasikov S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Copper-nickel sulfide ores are one of the main sources of platinum. One of the ways to extract precious metals from such ores involves melting of a concentrate in electric ore smelting furnaces, where the melt is divided into matte and slag. Platinum is generally concentrated in matte; however, some of it remains in the slag, thus leading to metal losses. In order to reduce platinum losses, the forms of platinum in these phases should be studied. It was found that during the melting of this ore, iron, nickel, and copper are reduced. The mineral composition of matte was studied. Platinum in matte is present in the form of intermetallics with Fe and Ni. The PtFe intermetallic is a dispersed needle formation with a length of 20 to 500 μm and a thickness of up to 10 μm. The size effect is revealed: the content of platinum in the PtFe intermetallic decreases with decreasing the thickness of needle formations. The decreases in the content of platinum in dispersed needle formations can be explained by an increase in the thermodynamic activity and changing properties of the dispersed substance and a corresponding increase in solubility. It was found that matte drops, together with their associated platinumcontaining particles of no more than 5-7 μm in size, were carried into the slag by gas bubbles using flotation. The conditions for the rise of a matte drop, together with a bubble in the slag, consist in the fact that the adhesive force of the drop with the bubble and the buoyancy force acting on the bubble must be greater than the gravity of the drop.